2016
DOI: 10.4070/kcj.2016.46.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs10757274 and rs2383206 Polymorphisms on 9p21 locus with Coronary Artery Disease in Turkish Population

Abstract: Background and ObjectivesGenetic predisposition is an important risk factor for coronary artery disease (CAD). In this study, we aimed to evaluate the impact of rs10757274 and rs2383206 polymorphisms in chromosome 9p21 on presence and severity of CAD in a Turkish population.Subjects and MethodsA total of 646 patients who underwent coronary angiography were included in this study. Coronary vessel score and Gensini score were calculated to assess the angiographic severity of CAD. Alleles of AA, AG, and GG were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Genetic features are crucial and constant risk factors for CAD pathogenesis. Recently, one study investigated the relationship between CAD and genetic predisposition and showed that 40% to 60% of the risk for CAD is related to genetic predisposition [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Genetic features are crucial and constant risk factors for CAD pathogenesis. Recently, one study investigated the relationship between CAD and genetic predisposition and showed that 40% to 60% of the risk for CAD is related to genetic predisposition [3]. …”
Section: Introductionmentioning
confidence: 99%
“…We found a significant relation between rs10757274 polymorphism and Gensini score. 2 We think that genome-wide association studies have a very important place in revealing the genetic background of CAD. We think that this valuable article 1 will also make a significant contribution to the literature on this subject.…”
mentioning
confidence: 99%
“…In our study, 2 we evaluate the impact of rs10757274 and rs2383206 polymorphisms in chromosome 9p21 on presence and severity of coronary artery disease (CAD) in a Turkish population. We found a significant relation between rs10757274 polymorphism and Gensini score.…”
mentioning
confidence: 99%